A process model of an effective Performance Appraisal System - Raman, Kunaraja Sita (1997)
This study thus attempted to develop a generic process model of a performance appraisal system based on the assumption that consideration of both psychometric and contextual factors In the design and Implementation process will lead to a more effective and acceptable performance appraisal The study was a qualitative study and employed a content analysis technique In its methodology, to identify the salient features of an effective performance appraisal system this first part of the study involved the collection of as much literature as possible, as available to the researcher, on performance appraisal theory and practices The literature was sourced from the resource centers of three local universities, which were in the form of books and research articles from journals and other materials. The objective of this part of the study was to identify the most important components of an effective performance appraisal after identifying the main components of the performance appraisal a further review of the research articles was done to extract more Information about the strengths and weaknesses of these components and its relevance to the effectiveness of the performance appraisal system Based on this information a generic process model of an effective performance appraisal system was developed This study Identified seven main steps that would contribute to the effectiveness of the performance appraisal process which are: i) set up the task force, II) Identify organisational variables; iii) determine purposes, IV) determine appraisal format and procedures; v) train and measure, VI) make HRM decisions, and, vii) evaluate performance appraisal effectiveness These components were then presented in a generic process model The model described the step by step process of designing and implementing an effective performance appraisal system